An atlas of burst oscillations and spectral properties in 4U 1728-34 - Straaten, Steve van (2001)
We study correlations between the burst properties and the position in the color-color diagram of the low mass X-ray binary 4U 1728-34 using 21 bursts found in two data sets obtained with the Rossi X-Ray Timing Explorer. Using spectral fits we analyze the spectral evolution during the bursts and determine the burst peak flux, temperature, rise time, and fluence. Using dynamical power spectra, we study the properties of the ∼ 363 Hz burst oscillations. We find correlations between fluence, peak flux, the occurrence of radius expansion, and the presence of burst oscillations and the position of the source in the color-color diagram. The radius expansion bursts with and without burst oscillations differ both with respect to where they occur in the color-color diagram and in how the radius expansion takes place. We compare our results with those of a similar study by Muno and coworkers for KS 1731-26. Both KS 1731-260 and 4U 1728-34 show more or less the same behavior with respect to the dependence of the presence/absence of the burst oscillations on the position of the source in the color-color diagram, but the dependence of most of the spectral burst parameters on the position in the color-color diagram is clearly different. We find that the systematic absence in 4U 1728-34 of burst oscillations in the "island" state of the color-color diagram is not explained by the bursts involving mixed H-He burning, as Cumming & Bildsten found may be the case in KS 1731-260.